Minha vida é o rock and roll: processos educativos na prática social do rock entre músicos da cidade de São Carlos - Pino, Mariel Perez (Universidade Federal de São Carlos, 2018)
The goal of this research was to study and to understand the educational processes from the social practice of Rock through the trajectories of the lives of some musicians from São Carlos. The theoretical purposes start from a perspective that Rock is a social practice and that through this practice the educational processes occur. Therefore, authors such as Oliveira et al., Brandão, Chacon, França, among others, constituted the basis for comprehending Rock as a social practice, both from the educational perspective and from music itself. Other authors such as Freire, Fiori and, again, Brandão supported the educational concepts, and Joly, Severino, Souza, Green, Lacorte, Galvão and others constituted the basis of the concepts regarding the musical education. The methodological proceeding used for the data collection was the “História Oral” method, in which the collaborators, in this case, Rock musicians, shared their musical and life stories in friendly meetings with the researcher. The hearing, the appreciation of the other the act of living with others and the solidarity were important aspects in this relation between researcher and collaborator. The authors used as reference to the “História Oral” method were Thompson, Meihy, Holanda and Alberti. The organizing of the data had as a reference point the Content Analysis, especially the one that was described by Franco. What came to be revealed as educational processes were those that were related to the musical learning, what made possible for the musicians to live their lives more fully and to contemplate the human relations and the life aspects in general. Some aspects like the importance of the family as a mediator of the musical and the human educational processes as well as the school and the learning within a group of friends emerge in the lives of these musicians in an effective manner as a result of the social practice in the Rock environment.
Rock and roll is my life: educational processes on the social practice of rock with São Carlos' musicians
Keywords: Rock; Processos educativos; Educação musical; Educational processes; Musical education; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM